MANEJO DA IRRIGAÇÃO E ADUBAÇÃO NITROGENADA NO FEIJOEIRO - CULTIVAR BRS ESTILO - KLIP, Dioph Vitor de Oliveira; LOPES, Adriano da Silva; FRANCO, Jhonatan da Silva; KRAESKI, Marcos Jeeferson; LOPES, Rafael da Silva; SILVA, Davi Pessoa (ANAIS DO ENIC, 2025)
-